NEW
New Website Launch
Experience the best way to solve previous year questions with mock tests (very detailed analysis), bookmark your favourite questions, practice etc...
1

WB JEE 2009

MCQ (Single Correct Answer)

The equation of the chord of he circle $${x^2} + {y^2} - 4x = 0$$ whose midpoint is (1, 0) is

A
y = 2
B
y = 1
C
x = 2
D
x = 1

Explanation

Equation of chord of circle

x2 + y2 + 2gx + 2fy + c = 0, where midpoint is (x1, y1) is T = S1

where T = xx1 + yy1 + g(x + x1) + f(y + y1) + c

and S1 = x$$_1^2$$ + y$$_1^2$$ + 2gx1 + 2fy1 + c

$$\therefore$$ Equation of chord of the circle x2 + y2 $$-$$ 4x = 0 whose midpoint is (1, 0) is

1x + 0y $$-$$ 2(x + 1) + 0(y + 0) = 12 + 02 $$-$$ 4 . 1

$$\Rightarrow$$ $$-$$ x $$-$$ 2 = $$-$$ 3 $$\Rightarrow$$ x = 1

2

WB JEE 2008

MCQ (Single Correct Answer)

The locus of the centres of the circles which touch both the axes is given by

A
$${x^2} - {y^2} = 0$$
B
$${x^2} + {y^2} = 0$$
C
$${x^2} - {y^2} = 1$$
D
$${x^2} + {y^2} = 1$$

Explanation

Let the coordinates of centre of circle are (h, k) and radius is a unit. Circle touches both the axes

h = a ..... (i)

k = a ..... (ii)

Eliminating a by squaring (i) and (ii) and then subtracting we get $${h^2} - {k^2} = 0$$

$$ \Rightarrow {x^2} - {y^2} = 0$$, which is required equation of locus.

3

WB JEE 2008

MCQ (Single Correct Answer)

The circles $${x^2} + {y^2} + 6x + 6y = 0$$ and $${x^2} + {y^2} - 12x - 12y = 0$$

A
cut orthogonally
B
touch each other internally
C
intersect in two points
D
touch each other externally

Explanation

Given equations of circles are

$${x^2} + {y^2} + 6x + 6y = 0$$ ..... (i)

$${x^2} + {y^2} - 12x - 12y = 0$$ .... (ii)

Centre $$\equiv$$ $${C_1}( - 3, - 3)$$

Centre $$\equiv$$ $${C_2}(6,6)$$

$${r_1} = \sqrt {9 + 9} = \sqrt {18} = 3\sqrt 2 $$

$${r_2} = \sqrt {36 + 36} = 6\sqrt 2 $$

$${C_1}{C_2} = \sqrt {{{(6 + 3)}^2} + {{(6 + 3)}^2}} = \sqrt {81 + 81} = 9\sqrt 2 $$

Since, $${C_1}{C_2} = {r_1} + {r_2} = 9\sqrt 2 $$

$$\therefore$$ both circles touch each other externally.

4

WB JEE 2008

MCQ (Single Correct Answer)

The equation $$(x - {x_1})(x - {x_2}) + (y - {y_1})(y - {y_2}) = 0$$ represents a circle whose centre is

A
$$\left( {{{{x_1} - {x_2}} \over 2},{{{y_1} - {y_2}} \over 2}} \right)$$
B
$$\left( {{{{x_1} + {x_2}} \over 2},{{{y_1} + {y_2}} \over 2}} \right)$$
C
$$({x_1},{y_1})$$
D
$$({x_2},{y_2})$$

Explanation

$$(x - {x_1})(x - {x_2}) + (y - {y_1})(y - {y_2}) = 0$$

This is equation of circle in diameter form where $$({x_1},{y_1})$$ and $$({x_2},{y_2})$$ are the end points of the diameter.

$$\therefore$$ Centre is midpoint of diameter $$ = \left( {{{{x_1} + {x_2}} \over 2},{{{y_1} + {y_2}} \over 2}} \right)$$.

Joint Entrance Examination

JEE Main JEE Advanced WB JEE

Graduate Aptitude Test in Engineering

GATE CSE GATE ECE GATE EE GATE ME GATE CE GATE PI GATE IN

Medical

NEET

CBSE

Class 12